Maculosin, a non-toxic antioxidant compound isolated from Streptomyces sp. KTM18 - Babita Paudel; Rukusha Maharjan; Prajwal Rajbhandari; Niraj Aryal; Saefuddin Aziz; Keshab Bhattarai; Bikash Baral; Rajani Malla; Hari Datta Bhattarai (Taylor & Francis Group, 2021)
Context Streptomyces species are prolific sources of bioactive secondary metabolites known especially for their antimicrobial and anticancer activities. Objective This study sought to isolate and characterize antioxidant molecules biosynthesized by Streptomyces sp. KTM18. The antioxidant potential of an isolated compound and its toxicity were accessed. Materials and methods The compound was purified using bioassay-guided chromatography techniques. Nuclear magnetic resonance (NMR) experiments were carried out for structure elucidation. The antioxidant potential of the isolated compound was determined using DPPH free radical scavenging assay. The toxicity of the isolated compound was measured using a brine shrimp lethality (BSL) assay. Results Ethyl acetate extract of Streptomyces sp. KTM18 showed more than 90% inhibition of DPPH free radical at 50 µg/mL of the test concentration. These data were the strongest among 13 Streptomyces isolates (KTM12-KTM24). The active molecule was isolated and characterized as maculosin (molecular formula, C14H16N2O3 as determined by the [M + H]+ peak at 261.1259). The DPPH free radical scavenging activity of pure maculosin was higher (IC50, 2.16 ± 0.05 µg/mL) than that of commercial butylated hydroxyanisole (BHA) (IC50, 4.8 ± 0.05 µg/mL). No toxicity was observed for maculosin (LD50, <128 µg/mL) in brine shrimp lethality assay (BSLA) up to the compound's antioxidant activity (IC50) concentration range. The commercial standard, berberine chloride, showed toxicity in BSLA with an LD50 value of 8.63 ± 0.15 µg/mL. Conclusions Maculosin may be a leading drug candidate in various cosmetic and therapeutic applications owing to its strong antioxidant and non-toxic properties.